Corruption and Violations of Conservation Rules: A Survey Experiment with Resource Users. (September 2016) - Sundström, Aksel
Summary: Small-scale corruption in government administrations that govern natural resources is believed to have a negative impact on conservation management. Yet, while corruption is said to obstruct the implementation of conservation policies, for instance as bribery may enable poaching in protected reserves, it is an underexplored area of research. This study investigates the effect of corruption, others' compliance behavior, and support for regulations on rule-violating intentions. In a between-subjects experiment, a sample of resource users active in South African small-scale fisheries ( N = 201) answered questions about rule-violating intentions after reading one of four scenarios, each depicting a different situation of corruption among officials that enforce regulations and compliance behavior of other resource users. The results show that resource users are more likely to state rule-violating intentions when corruption among inspectors is widespread. Moreover, the study provides further theoretical insights into the process in which corruption perceptions deter the willingness to follow rules: there is an interaction effect with support for conservation regulations, suggesting that the effect of corruption is stronger among individuals who are less supportive of such rules. These findings lend further support for the proposition that to improve the effectiveness of conservation policy, more effort is needed to reduce bribery among government officials, such as rangers and inspectors that enforce natural resource regulations.